Role of Sumenep Community Related Development of Culture-Based Tourism in Sumenep Regency - Sjaifurrachman, Sjaifurrachman; Fithry, Abshoril (PT. Riset Press International, 2024)
Sumenep is currently beginning to reveal its identity to the people of Indonesia, with its new motto Sumenep City of Keris. This motto is being promoted to the community to introduce the culture of the city. However, it is unfortunate that the opportunity of the keris industry in Sumenep Regency cannot provide a positive contribution to the economic welfare of the population in Sumenep Regency, mainly due to the lack of support from the Sumenep Regency Government in formulating policies, which is still not optimal. The sensitivity of the local government is indeed being tested, especially with the existence of Republic of Indonesia Emergency Law Number 12 of 1951. After Sumenep City declared itself as the city of keris, it is feared that there will be many people who will need legal protection if they want to bring heritage items such as keris in the future. This emergency law is also considered outdated or obsolete by researchers because it no longer suits the current situation and conditions. In this study, the researcher used normative research methods with legislative approach and case approach. The legal materials used are primary and secondary legal materials using descriptive analysis techniques, systematic techniques, and argumentation techniques. The goal is for the local government to educate and introduce the Culture and Local Wisdom in Sumenep Regency to the elements of the community, and for the people of Sumenep Regency to develop tourism based on Culture and Local Wisdom in Sumenep Regency.